Jurnal STRATEGI PENINGKATAN PEMBAYARAN MAHASISWA MELALUI VIRTUAL ACCOUNT DI UNIVERSITAS DHARMA WACANA - destrilia, intan (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2025)
Digital transformation in the higher education sector demands innovation in the tuition payment system. Dharmawacana University, as a private higher education institution, faces challenges in optimizing student payments. This study aims to identify strategies to improve the effectiveness and efficiency of student payments through virtual accounts. The method used is a qualitative study with a case study approach. The results show that the use of virtual accounts can improve payment order, accelerate administrative processes, and reduce manual financial workload. Recommended strategies include socialization, integration of academic systems with financial systems, collaboration with partner banks, and providing incentives for timely payments. This research is expected to serve as a reference in the development of digital payment systems in higher education.